Protection Motivation Theory-Based Questionnaire Validation to Predict Acceptance of Healthcare Workers towards Uptake of Pertussis Vaccine - Steven, Michal Christina; Jeffery, Stephen (Universiti Putra Malaysia Press, 2020)
Introduction: Pertussis is known to cause infection and reinfection to everyone irrespective of ages and countries. Therefore, adults do require vaccination for protection against pertussis infection especially the HCW. However, the pertussis vaccine coverage is low among HCW due to low-risk perception. Protection Motivation Theory (PMT) is one of the most cited theories to explain risk perception and intention to change. Therefore, we developed a questionnaire based on the subconstructs of the PMT to assess the acceptance of the pertussis vaccine amongst the HCWs in Sabah and Sarawak. The motive of this study is to validate this questionnaire to see its validity and reliability. Method: Data was collected using a self-administered questionnaire via an online survey (Monkey Survey). The questionnaire was given to 250 HCW. Items that were identified as a problem were modified to increase reliability. Further validation was done among 853 HCWs working in various parts of Sabah and Sarawak. Results: The Cronbach alpha of the overall construct of PMT during the first pilot study was 0.66 and improved to 0.82. Principal components factor analysis using varimax rotations showed that the first four factors explained 28%, 2%, 9% and 5% of the variance respectively. Both the one level and two-level modelling indicated that it’s a good fit model. Conclusion: The study instrument that was developed for the study has been tested and proven to be relevant to assess the risk perception of an HCW towards pertussis.